End-Point Results for Multivalued Mappings in Partially Ordered Metric Spaces - Ismat Beg; Hemant Kumar Nashine (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to prove end-point theorems for multivalued mappings satisfying comparatively a more general contractive condition in ordered complete metric spaces. Afterwards, we extend the results of previous sections and prove common end-point results for a pair of 𝒯-weakly isotone increasing multivalued mappings in the underlying spaces. Finally, we present common end point for a pair of 𝒯-weakly isotone increasing multivalued mappings satisfying weakly contractive condition.